1996
DOI: 10.1046/j.1525-1438.1996.06060477.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and prognostic factors in node-negative cervix cancer

Abstract: Relapse rates, mortality rates and possible prognostic factors were assessed in women with early‐stage, node‐negative cervix cancer. We identified 194 women who had a radical hysterectomy with histopathologically confirmed negative lymph nodes as primary treatment for FIGO stages IB and IIA cervix cancer between 1981 and 1990, at a single tertiary referral oncology centre. Each patient’s pathology was reviewed by two pathologists blinded to patient outcome. Clinical and demographic details were abstracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We found in our study that parametria were involved either by direct extension or in their lymph nodes in around 15% in the whole series, including patients with positive and negative pelvic lymph nodes, and in 36.4% when considering only patients with positive pelvic nodes. Although these figures are comparable with that of previous publications (30)(31)(32)(33)(34)(35)(36) , we found that the direct parametrial involvement from the tumoral cervix was higher than the affection of lymphatic vessels or nodes in the parametria (68.7 versus 31.3%). This is different from the previous published data using the interesting giant-section histological technique introduced by Burghardt and Pickel (27) some years ago that many groups of investigators have utilized for the parametrial study.…”
Section: Discussionmentioning
confidence: 99%
“…We found in our study that parametria were involved either by direct extension or in their lymph nodes in around 15% in the whole series, including patients with positive and negative pelvic lymph nodes, and in 36.4% when considering only patients with positive pelvic nodes. Although these figures are comparable with that of previous publications (30)(31)(32)(33)(34)(35)(36) , we found that the direct parametrial involvement from the tumoral cervix was higher than the affection of lymphatic vessels or nodes in the parametria (68.7 versus 31.3%). This is different from the previous published data using the interesting giant-section histological technique introduced by Burghardt and Pickel (27) some years ago that many groups of investigators have utilized for the parametrial study.…”
Section: Discussionmentioning
confidence: 99%
“…More reproducible methods using automated morphometry‐based systems have, however, also been unhelpful( 12, 13). A more recent study, including full histopathologic review by two pathologists in a node negative population, indicated a fourfold increase in the recurrence rate for patients with a grade 2 or 3 tumor( 14). Our findings are, however, in general concordance with the opinion that routinely obtained tumor grade is not predictive of recurrence in a lymph node negative population.…”
Section: Discussionmentioning
confidence: 99%
“…We found in our study that parametria were involved either by direct extension or in their lymph nodes in around 15% in the whole series, including patients with positive and negative pelvic lymph nodes, and in 36.4% when considering only patients with positive pelvic nodes. Although these figures are comparable with that of previous publications ( 30–36 ) , we found that the direct parametrial involvement from the tumoral cervix was higher than the affection of lymphatic vessels or nodes in the parametria (68.7 versus 31.3%). This is different from the previous published data using the interesting giant‐section histological technique introduced by Burghardt and Pickel ( 27 ) some years ago that many groups of investigators have utilized for the parametrial study.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the patients with negative pelvic lymph nodes, we found that between 85 patients with such condition, 77 patients (90.6%) had negative parametria and eight patients (9.4%) had positive parametria – similar or larger than other publications ( 3,17,36,43 ) – presenting statistical difference with positive pelvic nodes patients, and good specificity and good negative predictive value. Between these eight patients, three patients had parametrial positive nodes, and five direct parametrial compromise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation